Glass fiber reinforced halogen-free flame-retardant high glowing filament PBT modified material and preparation method thereof

By adding specific components and processes to the PBT material, glass fiber-reinforced halogen-free flame-retardant high-glow wire PBT modified material was developed, which solved the problems of poor material performance and environmental protection requirements in the prior art, and achieved high performance and excellent fire-resistance material preparation.

CN119552485APending Publication Date: 2025-03-04GUANGDONG SHUNDE SHUNYAN NEW MATERIALS

Patent Information

Application Number
CN202510119553.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art is difficult to develop halogen-free flame-retardant PBT materials that meet high heat wires, high performance and excellent fire resistance, and there are problems that cannot be met by environmental protection requirements.

Method used

Using glass fiber-reinforced halogen-free flame-retardant high-glow wire PBT modified material, materials with excellent flame-retardant and high mechanical properties are prepared by adding components such as organic phosphinates and inorganic hypophosphites, glow wire synergists and modified toughening agents, combined with efficient mixing and extrusion processes.

Benefits of technology

It realizes the high ignition temperature and stability of the material, reaches the flame retardant performance of UL94V0 level, meets the market demand for 750℃ ignition of the entire ignition of the 750℃ ignition, and meets the latest environmental protection control requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a glass fiber reinforced halogen-free flame-retardant high glowing filament PBT (polybutylene terephthalate) modified material and a preparation method thereof, and the glass fiber reinforced halogen-free flame-retardant high glowing filament PBT modified material comprises the following components in parts by weight: 28.5-44.5 parts of PBT resin, 0-10 parts of PET (polyethylene terephthalate) resin, 18-25 parts of a compound of organic hypophosphite and inorganic hypophosphite, 5-14 parts of a glowing filament synergist and 1-5 parts of a modified toughening agent, the invention relates to the technical field of high polymer materials, in particular to a high polymer material which comprises the following components in parts by weight: 0.1-0.5 part of an anti-transesterification agent, 0.2-1 part of an antioxidant, 0.2-1 part of a lubricant and 15-30 parts of glass fibers. The glowing filament has high mechanical properties and good fireproof performance, can meet the market demand that the glowing filament at 750 DEG C is not ignited in the whole process, meets the latest environment-friendly control requirement on the market, and has wide market application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a glass fiber reinforced halogen-free flame-retardant high glow-wire PBT modified material and a preparation method thereof. Background Art

[0002] As a tough engineering thermoplastic material, PBT (polybutylene terephthalate) is widely used in many fields such as electronics, automobile manufacturing, machinery and household appliances due to its excellent chemical stability, mechanical strength, electrical insulation properties and thermal stability. In recent years, with the improvement of environmental awareness, halogen-free flame-retardant PBT has gradually been favored by the market due to its environmental protection and safety.

[0003] Patent CN103992624A discloses a high glow-wire ignition temperature halogen-free flame-retardant reinforced PBT composition and preparation method, the product is composed of polybutylene terephthalate (PBT), halogen-free flame retardant, alkali-free glass fiber, toughening agent, antioxidant, lubricant, etc. This technical solution mainly uses alkyl hypophosphite, aluminum hypophosphite, and triphenyl phosphate to achieve the effects of flame retardancy and increasing the glow-wire temperature, but the addition of triphenyl phosphate cannot meet the environmental protection requirements of the existing market.

[0004] Patent CN105440597A discloses a high glow-wire flame-retardant reinforced PBT composite material and its preparation method. The high glow-wire flame-retardant reinforced PBT composite material comprises the following components: 50-60wt% polybutylene terephthalate, 20wt% composite flame retardant, 20wt% glass fiber and 0-10wt% grafting compatibilizer. The present invention selects a new flame retardant TDCP (tris(β,β'-dichloroisopropyl) phosphate) and an inorganic flame retardant filler attapulgite for compounding to obtain a better halogen-free flame-retardant reinforced PBT system. This technical solution contains halogen chlorine and cannot meet the halogen-free environmental protection requirements.

[0005] Patent CN117384471A discloses a halogen-free flame-retardant PBT composition, which belongs to the technical field of polymer materials. The technical solution mainly achieves flame retardant effect and increases glow wire temperature by compounding aluminum diethylphosphinate, (3-phenylene phosphate (2,6-methylphenyl) tetraester, hydroquinone bis (diphenyl phosphate)), melamine cyanurate, and hydrated zinc borate. The addition of hydrated zinc borate in this technical solution is likely to cause material degradation. Although the addition of chain extenders can improve the performance to a certain extent, the performance of the produced product is unstable.

[0006] Therefore, the development of glass fiber reinforced halogen-free flame retardant high glow wire PBT modified materials that meet the requirements of high glow wire, high performance, and excellent fire resistance has broad application prospects. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a glass fiber reinforced halogen-free flame retardant high glow wire PBT modified material, comprising the following components by weight: 28.5-44.5 parts by weight of PBT resin, 0-10 parts by weight of PET resin, 18-25 parts by weight of a compound of organic phosphite and inorganic phosphite, 5-14 parts by weight of a glow-wire synergist, 1-5 parts by weight of a modified toughening agent, 0.1-0.5 parts by weight of an anti-ester exchange agent, 0.2-1 parts by weight of an antioxidant, 0.2-1 parts by weight of a lubricant, and 15-30 parts by weight of glass fiber.

[0008] A method for preparing a glass fiber reinforced halogen-free flame-retardant high glow wire PBT modified material comprises the following steps: 1) PBT resin, PET resin, modified toughening agent, glow wire synergist and anti-esterification agent are mixed evenly with a high-speed mixer to obtain a pretreated mixture A; 2) The pretreated mixture A, the compound of the organic phosphite and the inorganic phosphite, the antioxidant and the lubricant are put into a blender, and mixed and stirred evenly to obtain a mixture B.

[0009] 3) Put the mixture B and glass fiber into a twin-screw extruder, heat them to melt and extrude them, the melt extrusion temperature is 180-260°C, and the screw speed is 300-600r / min, so as to obtain a glass fiber reinforced halogen-free flame retardant high glow wire PBT modified material.

[0010] Furthermore, the compound of the organic phosphite and the inorganic phosphite is a compound of diethyl aluminum phosphite and inorganic aluminum phosphite, and the compound weight ratio is 1:(4-10).

[0011] Furthermore, the glow-wire synergist is a compound of phosphazene flame retardant, melamine cyanurate and boehmite, and the weight ratio of the three is: 1: (3-3.5): (2-3); The phosphazene flame retardant is WSFR-5101, the free melamine content in the selected melamine cyanurate is less than 0.1%, and the boehmite is nano-boehmite with an average particle size of 10-20 nm.

[0012] Further, the intrinsic viscosity of the PBT resin is 0.65-1.0 dl / g, and the melt flow rate is 20-120 g / (10 min) under the test conditions of 250° C. / 2.16 kg; The intrinsic viscosity of the PET resin is 0.660-0.700 dl / g, and the melt flow rate is 90-110 g / (10 min) under the test conditions of 265° C. / 2.16 kg. The preferred model is KH2678C.

[0013] Furthermore, the anti-ester exchange agent is N,N-diisopropoxide calcium-1,3-phenyl phosphate; The antioxidant is one or more of antioxidant 1010, antioxidant 168, and antioxidant 1098; The lubricant is one or more of lubricant PETS, lubricant 540A, and silicone powder; The diameter of the glass fiber is 8-16 microns.

[0014] Furthermore, the preparation method of the modified toughening agent comprises: Step 1: Select a polyolefin elastomer, dissolve the polyolefin elastomer in a toluene organic solvent, and control the mass ratio of the polyolefin elastomer to toluene to be 1:(5-8); Prepare butyl acrylate and glycidyl methacrylate, add chain transfer agent dodecyl mercaptan, the molar ratio of butyl acrylate to glycidyl methacrylate is (3.5-4.5):1, and the amount of dodecyl mercaptan is 0.1%-0.3% of the total mass of butyl acrylate and glycidyl methacrylate to adjust the molecular weight of the polymer; The peroxide initiator tert-butyl hydroperoxide is selected, and the amount of tert-butyl hydroperoxide used is 0.8%-1.5% of the total mass of butyl acrylate and glycidyl methacrylate; The dissolved polyolefin elastomer, butyl acrylate and glycidyl methacrylate, dodecyl mercaptan and tert-butyl hydroperoxide are placed in a reaction kettle equipped with a stirring device (a stirring paddle adopts a double-layered spiral ribbon stirring paddle) and a reflux condensing device (a serpentine condensing tube is adopted); Step 2: nitrogen is introduced into the reactor at a rate of 22-28 mL / min, the reactor is heated to 90-110° C., the stirring rate of the reactor is controlled at 300-500 r / min, and the reaction is carried out for 4-5 hours under stirring conditions; After the reaction is completed, the reaction solution is slowly added to methanol, and then the precipitated product is collected by filtering equipment, and then washed with methanol, the weight ratio of methanol to the precipitated product is (5-10):1, the washing times are 3-5 times, and the washed product is dried in a vacuum oven, the vacuum degree in the vacuum oven is -0.08--0.1MPa, the drying temperature is 60-80°C, and the drying time is 12-18 hours to obtain a graft copolymer modified toughening agent; Step 3: dispersing nano-calcium carbonate in an ethanol solution, wherein the mass ratio of nano-calcium carbonate to ethanol is controlled at 1:6-1:8, adding an appropriate amount of titanate coupling agent, wherein the titanate coupling agent is 3%-4% of the mass of the nano-calcium carbonate, and treating the solution under ultrasonic conditions for 30-60 minutes, wherein the ultrasonic power is set to 220-280W and the frequency is 25-35kHz, and the treated nano-calcium carbonate is filtered through a filter device, wherein the filter device adopts a 0.2-0.5μm filter membrane, and then dried, wherein the drying temperature is 80-100°C and the drying time is 8-12 hours; The dried nano-calcium carbonate and the graft copolymer modified toughening agent are melt blended in a twin-screw extruder, the screw length-diameter ratio of the twin-screw extruder is controlled at (32-38):1, the temperature of each zone is set at 170-190°C, and the screw speed is 220-280r / min to form a nano-composite toughening agent; Step 4, blending the nanocomposite toughening agent and polystyrene in an internal mixer, setting the rotor speed of the internal mixer to 45-55 r / min, the temperature to 190-210° C., and the blending time to 6-8 minutes to obtain a modified toughening agent.

[0015] The present application discloses a glass fiber reinforced halogen-free flame retardant high glow wire PBT modified material and a preparation method thereof, which has the following beneficial effects: 1. By adding a compound of organic phosphinate and inorganic phosphite and a glow-wire synergist, the glow-wire ignition temperature and glow-wire stability of the material are improved, and the flame retardant UL94V0 level is achieved.

[0016] 2. By adding anti-ester exchange agent, the ester exchange reaction of the material can be inhibited, the mechanical properties of the material can be improved, and the thermal stability of the material can be improved.

[0017] 3. The glass fiber reinforced halogen-free flame-retardant high glow-wire PBT modified material prepared by the present invention has high mechanical properties, good fire resistance, can meet the market demand of 750°C glow-wire non-ignition throughout the whole process, and meets the latest environmental protection control requirements in the market. It has broad market application prospects, simple production process, strong operability, and is easy to promote and apply on a large scale.

[0018] 4. The modified toughening agent allows the polyolefin elastomer to be combined with butyl acrylate, etc., to optimize the molecular chain structure, form an elastic network, and effectively disperse stress. After being compounded, nano-calcium carbonate acts as a stress concentration point to induce silver streaks and shear bands, greatly enhancing impact resistance. Blending with polystyrene further synergistically improves tensile and bending properties; During the processing, its elasticity and flexibility reduce melt viscosity, enhance fluidity, reduce melt fracture and surface defects, and help to evenly distribute the glass fiber. From the perspective of stability, it is closely connected to the matrix material, and prevents migration and precipitation through chemical bonding and physical entanglement. Even in harsh environments such as high temperature and high humidity, it can ensure the long-term toughness and comprehensive performance of the material, thereby broadening the application range and service life of the material. DETAILED DESCRIPTION

[0019] The present invention will be further described in detail below in conjunction with specific embodiments. The embodiments of the present invention are provided for the purpose of illustration and description, and are not intended to be exhaustive or to limit the present invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described to better illustrate the principles and practical applications of the present invention, and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.

[0020] Embodiment, the preparation method of modified toughening agent comprises: Step 1: Select a polyolefin elastomer, dissolve the polyolefin elastomer in a toluene organic solvent, and control the mass ratio of the polyolefin elastomer to toluene to be 1:(5-8); Prepare butyl acrylate and glycidyl methacrylate, add chain transfer agent dodecyl mercaptan, the molar ratio of butyl acrylate to glycidyl methacrylate is (3.5-4.5):1, and the amount of dodecyl mercaptan is 0.1%-0.3% of the total mass of butyl acrylate and glycidyl methacrylate to adjust the molecular weight of the polymer; The peroxide initiator tert-butyl hydroperoxide is selected, and the amount of tert-butyl hydroperoxide used is 0.8%-1.5% of the total mass of butyl acrylate and glycidyl methacrylate; The dissolved polyolefin elastomer, butyl acrylate and glycidyl methacrylate, dodecyl mercaptan and tert-butyl hydroperoxide are placed in a reaction kettle equipped with a stirring device (a stirring paddle adopts a double-layered spiral ribbon stirring paddle) and a reflux condensing device (a serpentine condensing tube is adopted); Step 2: nitrogen is introduced into the reactor at a rate of 22-28 mL / min, the reactor is heated to 90-110° C., the stirring rate of the reactor is controlled at 300-500 r / min, and the reaction is carried out for 4-5 hours under stirring conditions; After the reaction is completed, the reaction solution is slowly added to methanol, and then the precipitated product is collected by filtering equipment, and then washed with methanol, the weight ratio of methanol to the precipitated product is (5-10):1, the washing times are 3-5 times, and the washed product is dried in a vacuum oven, the vacuum degree in the vacuum oven is -0.08--0.1MPa, the drying temperature is 60-80°C, and the drying time is 12-18 hours to obtain a graft copolymer modified toughening agent; Step 3: dispersing nano-calcium carbonate in an ethanol solution, wherein the mass ratio of nano-calcium carbonate to ethanol is controlled at 1:(6-8), adding an appropriate amount of titanate coupling agent, wherein the titanate coupling agent is 3%-4% of the mass of the nano-calcium carbonate, and treating the solution under ultrasonic conditions for 30-60 minutes, wherein the ultrasonic power is set to 220-280W and the frequency is 25-35kHz, and the treated nano-calcium carbonate is filtered through a filter device, wherein the filter device adopts a 0.2-0.5μm filter membrane, and then dried, wherein the drying temperature is 80-100°C and the drying time is 8-12 hours; The dried nano-calcium carbonate and the graft copolymer modified toughening agent are melt blended in a twin-screw extruder, the screw length-diameter ratio of the twin-screw extruder is controlled at (32-38):1, the temperature of each zone is set at 170-190°C, and the screw speed is 220-280r / min to form a nano-composite toughening agent; Step 4, blending the nanocomposite toughening agent and polystyrene in an internal mixer, setting the rotor speed of the internal mixer to 45-55 r / min, the temperature to 190-210° C., and the blending time to 6-8 minutes to obtain a modified toughening agent.

[0021] Embodiment 1, a glass fiber reinforced halogen-free flame retardant high glow wire PBT modified material, comprising the following components in parts by weight: 44.5 parts by weight of PBT resin, 0 parts by weight of PET resin, 18 parts by weight of a compound of an organic phosphite and an inorganic phosphite, 5 parts by weight of a glow wire synergist, 1 part by weight of a modified toughening agent, 0.1 parts by weight of an anti-ester exchange agent, 0.2 parts by weight of an antioxidant, 0.2 parts by weight of a lubricant, and 30 parts by weight of glass fiber; Example 2, a glass fiber reinforced halogen-free flame retardant high glow wire PBT modified material, comprising the following components in parts by weight: 38.8 parts by weight of PBT resin, 5 parts by weight of PET resin, 20 parts by weight of a compound of an organic phosphite and an inorganic phosphite, 8 parts by weight of a glow wire synergist, 2 parts by weight of a modified toughening agent, 0.2 parts by weight of an anti-ester exchange agent, 0.5 parts by weight of an antioxidant, 0.5 parts by weight of a lubricant, and 25 parts by weight of glass fiber; Example 3, a glass fiber reinforced halogen-free flame retardant high glow wire PBT modified material, comprising the following components in parts by weight: 35.1 parts by weight of PBT resin, 7 parts by weight of PET resin, 22 parts by weight of a compound of an organic phosphite and an inorganic phosphite, 11 parts by weight of a glow wire synergist, 3 parts by weight of a modified toughening agent, 0.5 parts by weight of an anti-ester exchange agent, 0.7 parts by weight of an antioxidant, 0.7 parts by weight of a lubricant, and 20 parts by weight of glass fiber; Example 4, a glass fiber reinforced halogen-free flame retardant high glow wire PBT modified material, comprising the following components in parts by weight: 28.5 parts by weight of PBT resin, 10 parts by weight of PET resin, 25 parts by weight of a compound of an organic phosphite and an inorganic phosphite, 14 parts by weight of a glow wire synergist, 5 parts by weight of a modified toughening agent, 0.5 parts by weight of an anti-ester exchange agent, 1 part by weight of an antioxidant, 1 part by weight of a lubricant, and 15 parts by weight of glass fiber; Comparative Example 1, a PBT modified material, comprising the following components in parts by weight: 45.5 parts by weight of PBT resin, 0 parts by weight of PET resin, 18 parts by weight of diethyl aluminum phosphite, 0 parts by weight of inorganic aluminum hypophosphite, 0 parts by weight of a compound of diethyl aluminum phosphite and inorganic aluminum hypophosphite, 5 parts by weight of a glow-wire synergist, 0 parts by weight of a glow-wire synergist a, 0 parts by weight of a glow-wire synergist b, 0 parts by weight of a glow-wire synergist c, 1 part by weight of a modified toughening agent, 0.1 parts by weight of an anti-ester exchange agent, 0.2 parts by weight of an antioxidant, 0.2 parts by weight of a lubricant, and 30 parts by weight of glass fiber; Comparative Example 2, a PBT modified material, comprising the following components in parts by weight: 45.5 parts by weight of PBT resin, 0 parts by weight of PET resin, 0 parts by weight of diethyl aluminum phosphite, 18 parts by weight of inorganic aluminum hypophosphite, 0 parts by weight of a compound of diethyl aluminum phosphite and inorganic aluminum hypophosphite, 5 parts by weight of a glow-wire synergist, 0 parts by weight of a glow-wire synergist a, 0 parts by weight of a glow-wire synergist b, 0 parts by weight of a glow-wire synergist c, 1 part by weight of a modified toughening agent, 0.1 parts by weight of an anti-ester exchange agent, 0.2 parts by weight of an antioxidant, 0.2 parts by weight of a lubricant, and 30 parts by weight of glass fiber; Comparative Example 3, a PBT modified material, comprising the following components in parts by weight: 46.3 parts by weight of PBT resin, 7 parts by weight of PET resin, 0 parts by weight of aluminum diethylphosphinate, 0 parts by weight of inorganic aluminum hypophosphite, 22 parts by weight of a compound of aluminum diethylphosphinate and inorganic aluminum hypophosphite, 0 parts by weight of a glow-wire synergist, 0 parts by weight of a glow-wire synergist a, 0 parts by weight of a glow-wire synergist b, 0 parts by weight of a glow-wire synergist c, 3 parts by weight of a modified toughening agent, 0.3 parts by weight of an anti-ester exchange agent, 0.7 parts by weight of an antioxidant, 0.7 parts by weight of a lubricant, and 20 parts by weight of glass fiber; Comparative Example 4, a PBT modified material, comprising the following components in parts by weight: 35.6 parts by weight of PBT resin, 7 parts by weight of PET resin, 0 parts by weight of aluminum diethylphosphinate, 0 parts by weight of inorganic aluminum hypophosphite, 22 parts by weight of a compound of aluminum diethylphosphinate and inorganic aluminum hypophosphite, 11 parts by weight of a glow-wire synergist, 0 parts by weight of a glow-wire synergist a, 0 parts by weight of a glow-wire synergist b, 0 parts by weight of a glow-wire synergist c, 3 parts by weight of a modified toughening agent, 0 parts by weight of an anti-ester exchange agent, 0.7 parts by weight of an antioxidant, 0.7 parts by weight of a lubricant, and 20 parts by weight of glass fiber; Comparative Example 5, a PBT modified material, comprising the following components in parts by weight: 35.3 parts by weight of PBT resin, 7 parts by weight of PET resin, 0 parts by weight of aluminum diethylphosphinate, 0 parts by weight of inorganic aluminum hypophosphite, 22 parts by weight of a compound of aluminum diethylphosphinate and inorganic aluminum hypophosphite, 0 parts by weight of a glow-wire synergist, 11 parts by weight of a glow-wire synergist a, 0 parts by weight of a glow-wire synergist b, 0 parts by weight of a glow-wire synergist c, 3 parts by weight of a modified toughening agent, 0.3 parts by weight of an anti-ester exchange agent, 0.7 parts by weight of an antioxidant, 0.7 parts by weight of a lubricant, and 20 parts by weight of glass fiber; Comparative Example 6, a PBT modified material, comprising the following components in parts by weight: 35.3 parts by weight of PBT resin, 7 parts by weight of PET resin, 0 parts by weight of aluminum diethylphosphinate, 0 parts by weight of inorganic aluminum hypophosphite, 22 parts by weight of a compound of aluminum diethylphosphinate and inorganic aluminum hypophosphite, 0 parts by weight of a glow-wire synergist, 0 parts by weight of a glow-wire synergist a, 11 parts by weight of a glow-wire synergist b, 0 parts by weight of a glow-wire synergist c, 3 parts by weight of a modified toughening agent, 0.3 parts by weight of an anti-ester exchange agent, 0.7 parts by weight of an antioxidant, 0.7 parts by weight of a lubricant, and 20 parts by weight of glass fiber; Comparative Example 7, a PBT modified material, comprising the following components in parts by weight: 35.3 parts by weight of PBT resin, 7 parts by weight of PET resin, 0 parts by weight of aluminum diethylphosphinate, 0 parts by weight of inorganic aluminum hypophosphite, 22 parts by weight of a compound of aluminum diethylphosphinate and inorganic aluminum hypophosphite, 0 parts by weight of a glow-wire synergist, 0 parts by weight of a glow-wire synergist a, 0 parts by weight of a glow-wire synergist b, 11 parts by weight of a glow-wire synergist c, 3 parts by weight of a modified toughening agent, 0.3 parts by weight of an anti-ester exchange agent, 0.7 parts by weight of an antioxidant, 0.7 parts by weight of a lubricant, and 20 parts by weight of glass fiber; Comparative Example 8, a PBT modified material, comprising the following components in parts by weight: 27.5 parts by weight of PBT resin, 10 parts by weight of PET resin, 0 parts by weight of aluminum diethylphosphinate, 0 parts by weight of inorganic aluminum hypophosphite, 25 parts by weight of a compound of aluminum diethylphosphinate and inorganic aluminum hypophosphite, 15 parts by weight of a glow-wire synergist, 0 parts by weight of a glow-wire synergist a, 0 parts by weight of a glow-wire synergist b, 0 parts by weight of a glow-wire synergist c, 5 parts by weight of a modified toughening agent, 0.5 parts by weight of an anti-ester exchange agent, 1 part by weight of an antioxidant, 1 part by weight of a lubricant, and 15 parts by weight of glass fiber; In the above comparative examples, the glow-wire synergist a does not contain phosphazene flame retardant; the glow-wire synergist b does not contain melamine cyanurate; and the glow-wire synergist c does not contain boehmite.

[0022] On the basis of the above embodiments and comparative examples, in the above embodiments, the compound of the organic phosphinate and the inorganic phosphinate is a compound of diethyl aluminum phosphinate and inorganic aluminum phosphite, and the compound weight ratio is 4.5:5.5; The glow-wire synergist is a compound of phosphazene flame retardant, melamine cyanurate and boehmite, and the weight ratio of the three is 1:3:2.5; The phosphazene flame retardant is WSFR-5101, the free melamine content in the selected melamine cyanurate is less than 0.1%, and the boehmite is nano-boehmite with an average particle size of 10-20 nm; The intrinsic viscosity of PBT resin is 0.65-1.0dl / g, and the melt flow rate is 20-120g / 10min under the test conditions of 250℃ / 2.16kg; The intrinsic viscosity of PET resin is 0.660-0.700 dl / g, and the melt flow rate is 90-110 g / 10 min under the test conditions of 265°C / 2.16 kg. The preferred model is KH2678C; The anti-esterification agent is N,N-diisopropoxide calcium-1,3-phenyl phosphate; The modified toughening agent adopts the modified toughening agent prepared in the embodiment; The antioxidant is a mixture of antioxidant 1010 and antioxidant 168 at a ratio of 1:1; The lubricant is a mixture of lubricant PETS and lubricant 540A at a ratio of 1:1; The diameter of glass fibers is 8-16 microns.

[0023] The above-mentioned embodiments and comparative examples are all prepared by the following preparation method, comprising the following steps: 1) PBT resin, PET resin, modified toughening agent, glow wire synergist and anti-esterification agent are mixed evenly with a high-speed mixer to obtain a pretreated mixture A; 2) The pretreated mixture A, the compound of the organic phosphite and the inorganic phosphite, the antioxidant and the lubricant are put into a blender, and mixed and stirred evenly to obtain a mixture B.

[0024] 3) Put the mixture B and glass fiber into a twin-screw extruder, heat them to melt and extrude them, the melt extrusion temperature is 180-260°C, and the screw speed is 300-600r / min, so as to obtain a glass fiber reinforced halogen-free flame retardant high glow wire PBT modified material.

[0025] The material properties of Examples 1-4 and Comparative Examples 1-8 were measured: Referring to international standards ISO 527, ISO 178 and ISO 180, the tensile strength, flexural strength, flexural modulus and Izod notched impact strength of the PET modified materials of each embodiment and each comparative example were tested respectively; Referring to the standard UL-94, the flame retardant grades of the PET modified materials of each embodiment and each comparative example were tested respectively; Using an injection molding machine, the PET modified materials of each embodiment and each comparative example were respectively used for injection molding for 4 hours continuously, and the color of the corresponding injection molded products was observed and checked to see whether they were normal, whether the demoulding was normal, and whether there was a water outlet break phenomenon; A laser engraving machine was used with a focal length of 26.5 mm, a laser engraving speed of 2000 mm / s, a laser power of 95%, and a frequency of 20 KHz to detect the engraving effects of the PET modified materials of each embodiment and each comparative example.

[0026] Table 1 Comparative Examples 1-8 Material Performance Table Table 2 Material properties of Examples 1-4 According to Table 1, the data of Comparative Examples 1 and 2 show that organic phosphites are helpful to improve the fluidity and thermal stability of the material, but cannot improve the glow-wire temperature of the material; inorganic phosphites are helpful to improve the glow-wire temperature and glow-wire stability of the material, but affect the fluidity of the material, making the melt index of the material lower, and the material is prone to discoloration during processing, and the temperature resistance of the material is deteriorated. Inorganic phosphites are more helpful to improve the glow-wire temperature of the material than organic phosphites, because the phosphorus content in inorganic phosphites is ≥40%, and the phosphorus content in organic phosphites is ≥23%. The phosphorus content refers to the phosphorus content per unit weight. The phosphorus content in inorganic phosphites is significantly higher than that in organic phosphites, and the higher the phosphorus and nitrogen content, the more beneficial it is to improve the glow-wire temperature of the material.

[0027] The data of Comparative Examples 3, 5, 6 and 7 show that the compound of glow-wire synergist phosphazene flame retardant, melamine cyanurate and boehmite can effectively improve the glow-wire temperature and glow-wire stability of the material. Among them, the phosphazene flame retardant contains phosphorus and nitrogen, which is beneficial to improving the glow-wire temperature of the material and can improve the fluidity of the material; melamine cyanurate contains rich nitrogen, which can effectively improve the glow-wire temperature of the material; boehmite contains aluminum oxide, which absorbs heat under high temperature conditions and can effectively improve the dark fire phenomenon that occurs during the glow-wire test. The glow-wire synergist phosphazene flame retardant, melamine cyanurate and boehmite are used in combination, and the improvement effect of the glow-wire is better. When used alone, the glow-wire is unstable.

[0028] The data of Comparative Example 4 show that the anti-ester exchange agent can effectively inhibit the ester exchange reaction between the hydroxyl group and the carboxyl group and the resin, which helps to improve the mechanical properties of the material and the temperature resistance of the material, so that the material remains stable during the processing.

[0029] The data of Comparative Example 8 show that when the amount of glow-wire synergist added is too high, the mechanical properties of the material begin to seriously decay, the brittleness of the material becomes more serious, and it is difficult to meet the use environment of the material.

[0030] Based on the data in Table 1 and Table 2, it can be seen that the addition of glow-wire synergist will cause a slight decrease in the performance of the material. The higher the addition amount, the more obvious the decrease. However, it has a significant effect on increasing the glow-wire ignition temperature and improving the glow-wire stability. The above technical effects can be obtained by using the melt index and glow-wire data. In the above technical scheme, the glass fiber reinforced halogen-free flame retardant high glow-wire PBT modified material prepared in Example 1 has the best comprehensive mechanical properties, which meets the requirements of high glow-wire, high performance, and excellent fire resistance.

[0031] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.

Claims

1. A glass fiber reinforced halogen-free flame retardant high glow wire PBT modified material, characterized in that: It comprises the following components by weight: 28.5-44.5 parts by weight of PBT resin, 0-10 parts by weight of PET resin, 18-25 parts by weight of a compound of an organic phosphite and an inorganic phosphite, 5-14 parts by weight of a glow-wire synergist, 1-5 parts by weight of a modified toughening agent, 0.1-0.5 parts by weight of an anti-ester exchange agent, 0.2-1 parts by weight of an antioxidant, 0.2-1 parts by weight of a lubricant, and 15-30 parts by weight of glass fiber; The modified toughening agent is prepared by using polyolefin elastomer, toluene, butyl acrylate, dodecyl mercaptan, tert-butyl hydroperoxide, methanol, nano calcium carbonate, ethanol, titanate coupling agent and polystyrene through a graft copolymerization and melt mixing method.

2. A method for preparing the glass fiber reinforced halogen-free flame retardant high glow wire PBT modified material as claimed in claim 1, characterized in that: The following steps are involved: 1) PBT resin, PET resin, modified toughening agent, glow wire synergist and anti-esterification agent are mixed evenly with a high-speed mixer to obtain a pretreated mixture A; 2) putting the pretreated mixture A, the compound of the organic phosphite and the inorganic phosphite, the antioxidant and the lubricant into a blender, mixing and stirring them evenly to obtain a mixture B; 3) Put the mixture B and glass fiber into a twin-screw extruder, heat them to melt and extrude them, the melt extrusion temperature is 180-260°C, and the screw speed is 300-600r / min, so as to obtain a glass fiber reinforced halogen-free flame retardant high glow wire PBT modified material.

3. The preparation method of the glass fiber reinforced halogen-free flame retardant high glow wire PBT modified material according to claim 2, characterized in that: The compound of the organic phosphite and the inorganic phosphite is a compound of diethyl aluminum phosphite and inorganic aluminum phosphite, and the compound weight ratio is 1: (4-10).

4. The method for preparing the glass fiber reinforced halogen-free flame retardant high glow wire PBT modified material according to claim 2, characterized in that: The glow-wire synergist is a compound of phosphazene flame retardant, melamine cyanurate and boehmite, and the weight ratio of the three is: 1: (3-3.5): (2-3); The phosphazene flame retardant is WSFR-5101, the free melamine content in the selected melamine cyanurate is less than 0.1%, and the boehmite is nano-boehmite with an average particle size of 10-20 nm.

5. The method for preparing the glass fiber reinforced halogen-free flame retardant high glow wire PBT modified material according to claim 2, characterized in that: The intrinsic viscosity of the PBT resin is 0.65-1.0 dl / g, and the melt flow rate is 20-120 g / 10 min under the test conditions of 250° C. / 2.16 kg; The intrinsic viscosity of the PET resin is 0.660-0.700 dl / g, and the melt flow rate is 90-110 g / 10 min under the test conditions of 265° C. / 2.16 kg.

6. The method for preparing the glass fiber reinforced halogen-free flame retardant high glow wire PBT modified material according to claim 2, characterized in that: The anti-ester exchange agent is N, N-diisopropoxide calcium-1, 3-phenyl phosphate; The antioxidant is one or more of antioxidant 1010, antioxidant 168, and antioxidant 1098; The lubricant is one or more of lubricant PETS, lubricant 540A, and silicone powder; The diameter of the glass fiber is 8-16 microns.

7. The method for preparing the glass fiber reinforced halogen-free flame retardant high glow wire PBT modified material according to claim 2, characterized in that: The preparation method of the modified toughening agent comprises: Step 1: Select a polyolefin elastomer and dissolve the polyolefin elastomer in a toluene organic solvent; Prepare butyl acrylate and glycidyl methacrylate, add chain transfer agent dodecyl mercaptan; The peroxide initiator tert-butyl hydroperoxide is selected; The dissolved polyolefin elastomer, butyl acrylate and glycidyl methacrylate, dodecyl mercaptan and tert-butyl hydroperoxide are placed in a reaction kettle equipped with a stirring device and a reflux condensing device; Step 2: introduce nitrogen into the reactor, heat the reactor to 90-110°C, and react for 4-5 hours under stirring; After the reaction is completed, the reaction solution is slowly added into methanol, and then the precipitated product is collected by filtering equipment, and then washed with methanol, and the washed product is dried in a vacuum oven to obtain a graft copolymer modified toughening agent; Step 3: Disperse the nano-calcium carbonate in an ethanol solution, add an appropriate amount of titanate coupling agent, and treat under ultrasonic conditions for 30-60 minutes. The treated nano-calcium carbonate is filtered through a filtering device and then dried at a drying temperature of 80-100° C. for 8-12 hours. The dried nano-calcium carbonate and the graft copolymerized toughening agent are melt-blended in a twin-screw extruder to form a nano-composite toughening agent; Step 4: blending the nanocomposite toughening agent with polystyrene in an internal mixer to obtain a modified toughening agent.

8. The method for preparing the glass fiber reinforced halogen-free flame retardant high glow wire PBT modified material according to claim 7, characterized in that: In the step 1, the mass ratio of the polyolefin elastomer to toluene is controlled to be 1:(5-8), the molar ratio of butyl acrylate to glycidyl methacrylate is (3.5-4.5):1, the amount of dodecyl mercaptan used is 0.1%-0.3% of the total mass of butyl acrylate and glycidyl methacrylate, and the amount of tert-butyl hydroperoxide used is 0.8%-1.5% of the total mass of butyl acrylate and glycidyl methacrylate.

9. The method for preparing the glass fiber reinforced halogen-free flame retardant high glow wire PBT modified material according to claim 7, characterized in that: In the step 3, the mass ratio of nano-calcium carbonate to ethanol is controlled at 1:(6-8), and the titanate coupling agent is 3%-4% of the mass of the nano-calcium carbonate.

10. The method for preparing the glass fiber reinforced halogen-free flame retardant high glow wire PBT modified material according to claim 7, characterized in that: In step 4, the rotor speed of the internal mixer is set to 45-55 r / min, the temperature is 190-210° C., and the blending time is 6-8 minutes.

Citation Information

Patent Citations

  • High-glow-wire flame-retardant reinforced type PBT composite material and preparation method thereof

    CN105440597A

  • Halogen-free flame-retardant PBT composition and preparation method thereof

    CN117384471A

  • High-glowing filament initiation temperature halogen-free flame-retardant reinforced PBT (Polybutylene Terephthalate) composition and preparation method thereof

    CN103992624A

  • Toughened modified PC / PET alloy material with high impact resistant performance and preparation method thereof

    CN104710744A

  • Flame retardant PBT material for laser marking of black on blue and preparation method thereof

    CN109929225A

Cited By

  • High glowing filament flame-retardant reinforced high-performance PET modified material and preparation method thereof

    CN119798939A

  • Polybutylene terephthalate resin composition as well as preparation method and application thereof

    CN120098418A